Penerapan Metode Konferensi untuk Meningkatkan Hasil Belajar Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam - Haryati, Haryati; Anggraini , Deriati; Firdayani , Firdayani (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ learning outcomes in Islamic Religious Education (PAI) through the implementation of the Conference discussion method. This method is designed to enhance student engagement, broaden their perspectives, and develop critical and analytical thinking skills. The study employs a classroom action research (CAR) design with two cycles, each consisting of planning, implementation, observation, and reflection stages. The findings indicate that the Conference discussion method significantly improved students’ learning outcomes, with the average score increasing from 73.4 in the first cycle to 86.66 in the second cycle. Additionally, students demonstrated improvements in confidence and communication skills. Although the results were positive, some students still required further guidance. Therefore, this approach needs to be continuously refined to maximize its effectiveness in Islamic Religious Education learning.